2019
DOI: 10.1037/spy0000137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a planning intervention on physical activity behavior in an RCT: Intention strength as moderator and action planning, coping planning, and coping self-efficacy as mediators.

Abstract: Planning is an effective strategy to translate intentions into behavior, and planning interventions can facilitate behavior change. The present study aimed to examine when and how a planning intervention facilitates physical activity. Therefore, the moderating role of intention strength and the mediating role of the specificity of action plans, coping plans, as well as coping self-efficacy were investigated. Furthermore, intention strength was tested as a moderator of the mediation effect. Hypotheses were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 56 publications
0
27
1
Order By: Relevance
“…Martens et al reported + 0.7 days/week and + 35mins/week of completing vigorous PA at 1-month follow-up in participants who received a single session motivational intervention versus a standard educational brochure [ 66 ]. In studies by Bray et al and Pfeffer et al participants reported +78mins/week and + 0.86 h/week greater MVPA at 6-weeks and 1-week follow up respectively, following single session interventions which focused on action planning for PA versus no/alternative intervention control [ 63 , 69 ]. Conner et al and Cooke et al found single session interventions involving affective messaging and self-affirmation around physical activity behaviours were effective compared with no intervention and non-affirmation at 3 and 1-week follow-up respectively, however actual change in time spent completing PA were not reported [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Martens et al reported + 0.7 days/week and + 35mins/week of completing vigorous PA at 1-month follow-up in participants who received a single session motivational intervention versus a standard educational brochure [ 66 ]. In studies by Bray et al and Pfeffer et al participants reported +78mins/week and + 0.86 h/week greater MVPA at 6-weeks and 1-week follow up respectively, following single session interventions which focused on action planning for PA versus no/alternative intervention control [ 63 , 69 ]. Conner et al and Cooke et al found single session interventions involving affective messaging and self-affirmation around physical activity behaviours were effective compared with no intervention and non-affirmation at 3 and 1-week follow-up respectively, however actual change in time spent completing PA were not reported [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 21 gender-neutral studies, 14 were effective (67%). Seven studies (54%) demonstrated significant changes in time completing PA [63][64][65][66][67][68][69], three and two studies demonstrated significant changes in exercise frequency [66,70,71] and steps per day respectively [72,73], and one study each for gym attendance [74], meeting physical activity guidelines [75], and physical activity score [76]. Martens et al reported + 0.7 days/week and + 35mins/week of completing vigorous PA at 1-month follow-up in participants who received a single session motivational intervention versus a standard educational brochure [66].…”
Section: Physical Activity Outcomesmentioning
confidence: 99%
“…Participants of the control group read a text from a popular scientific journal without reference to PA behavior in the presence of the experimenter for about 15 min [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The coping planning scale was introduced by the words “I have made detailed plans regarding...,” followed by 4 items (e.g., “...what to do if something intervenes”). A mean value for coping planning was calculated from the 4 items, and the higher the score, the more specific the individual’s plans in terms of how to cope with difficulties and how to overcome obstacles [ 21 ]. The analyses revealed good (Cronbach’s alpha; action planning, α = 0.88; coping planning, α = 0.84) to very good (total planning score, α = 0.91) internal consistencies for both scales.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation